A bibliometric analysis of research on flipped learning in EFL speaking classroom - Tuilan, Jeane; Tuerah, Ignatius Javier Couturier; Sumual, Hendro M.; Mantiri, Jeane; Mahayanti, Ni Wayan Surya (Edelweiss Applied Science and Technology, 2024)
This study offers a bibliometric analysis of research on the flipped learning model in EFL speaking classrooms. The intention here is to grasp the trends, implications and core tenets related in this pedagogical method. Data and methods. We used Dimensions database to annotate 2016-2024 articles. A total of 20 articles were selected and analysed by VOSviewer, a bibliometric network visualization analytical tool. Our results suggest that the volume of research activity ebbs and flows over time, with periods of high activity in response to external events (such as a global pandemic driven by an emergence of Covid19). The disciplines that have received the greatest number of publications in research on flipped learning based by categories were "Education," followed closely by a cluster related to “Language”, “Communication and Culture” as well as “Linguistics” (showing once again how interdisciplinary this approach has become). Teaching strategies, student engagement and the psychology of flipped learning were common topics among all articles. Innovative, technology-enhanced methods to promote English as a Foreign Language (EFL) speaking skills are posited as playing a prominent part in the analysis. Longitudinal studies to explore the effects of flipped learning over time are warranted. This is supported by the need for regional research on different cultural and educational settings to test its applicability elsewhere. Finally, because there will be practical issues teachers face trying to do flipped learning that influences its effectiveness. Flipped learning is a promising method to improve EFL education. More research should explore the gaps and support its implementation in different educational environments.